Short-term effect of Transcutaneous Spinal Cord Stimulation in patients with multiple sclerosis: a randomized sham-controlled crossover study - Spieker, Eira Lotta; Hoffmann, Marie; Otto, Carolin; Ruprecht, Klemens; Harms, Lutz; Schauer, Thomas; Salchow-Hömmen, Christina; Wenger, Nikolaus (Frontiers in Neurology, 2025)
BackgroundGait deficits and leg spasticity are frequent symptoms in Primary and Secondary Progressive Multiple Sclerosis (PPMS and SPMS). Transcutaneous spinal cord stimulation (tSCS) may alleviate these symptoms through the reduction of spinal hyperexcitability. We conducted a single-center, randomized, sham-controlled clinical crossover study (German Clinical Trials Register: DRKS00023357, https://www.drks.de/search/en) in patients with PPMS and SPMS to assess the therapy effects of tSCS on spasticity and gait in the post stimulation period.MethodsTwenty participants were included in the study to receive tSCS and sham interventions on two separate study days in randomized order. Patients and examiners were blinded to the sequence allocation, which was performed using a quasi-randomized procedure to ensure balanced group sizes. The tSCS intervention consisted of biphasic pulses applied for 30 min at 50 Hz to lumbar spinal segments. Assessments were carried out before and immediately after each intervention. The primary outcome was defined as the Modified Ashworth Scale (MAS) sum score for bilateral leg spasticity. Secondary outcomes included unilateral MAS sum scores and clinical gait assessments. We used inertial sensors to monitor gait kinematics and EMG to record Posterior-Root-Muscle-Reflexes (PRM-reflex) in leg muscles.ResultsFollowing the exclusion of two dropouts and two participants who did not reach the target intensity, sixteen participants, evenly distributed across the two intervention sequences, were included in the analysis. In comparison to sham, tSCS had a small effect on bilateral MAS sum score (effect size = −0.25, p = 0.12, CI: −5.67–0.63, for Generalized Equation Estimation), which didn't reach significance. More patients showed an improvement in stimulation condition (10 out of 16 patients) than in sham condition (7 out of 16 patients). We observed negligible effects of tSCS on clinical gait tests, kinematic parameters and PRM-reflex recruitment.ConclusionOur results showed that tSCS had a small but no significant effect on spasticity. A reduction of spasticity did not immediately translate into an improvement of gait performance.Clinical trials registrationhttps://www.drks.de/search/en, identifier: DRKS00023357.